Integrating Fine Motor Skill Development with Qur'anic Memorization Activities in Islamic Early Childhood Education: A Teacher Role Analysis - Sarmila; Heny Irliany; Fachrul Rozie (Universitas Al-Hikmah Indonesia, 2026)
This study aims to analyze the role of teachers in fine motor skill learning among children aged 5–6 years at TK Tahfidz RHQ Samarinda, an early childhood education institution that integrates Qur’anic memorization (tahfidz) with child development programs. This study employed a qualitative approach using a case study method, focusing on the educational setting as the research context. The participants included classroom teachers and children aged 5–6 years, while the object of the study focused on teachers’ roles in planning, implementing, and evaluating fine motor skill learning integrated with tahfidz activities. Data were collected through observation, in-depth interviews, and documentation and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that teachers play strategic roles as planners, facilitators, and evaluators by integrating fine motor activities into tahfidz learning, including writing hijaiyah letters, coloring simple calligraphy, and engaging children in manipulative activities that support Qur’anic memorization readiness. The novelty of this study lies in the integration of fine motor skill development with tahfidz-based learning in an Islamic early childhood education setting, an area that remains underexplored in previous studies. The findings imply the importance of developing contextual and integrative learning strategies to optimize children’s fine motor development while simultaneously supporting holistic learning readiness.